Reading Maulid al-Dība’i through the Lens of Genetic Structuralism: Between Text, Context, and Sectarian Polemics - Fina Mazida Husna; Ibnu Burdah; Muhyar Fanani; Nely Irnik Darajah; Ahmad Munadirin (LISANIA: Journal of Arabic Education and Literature, 2025)
Maulid al-Dība'i is one of the most popular religious literary texts in the Islamic tradition, especially among traditional Sunni Muslims in Indonesia. Recently, controversy has emerged regarding the sectarian affiliation of its author, Al-Dība'i, who is accused of being a Zaidiyah Shiite due to his praise of the Ahlul Bait without mentioning the main companions. This debate has prompted differing responses concerning the sectarian content of the text. This study applies Lucien Goldmann's genetic structuralism approach to analyze Maulid al-Dība'i by examining both its internal textual structure and its socio-historical context. Using qualitative interpretive, historical, and textual methods, the research analyzes a controversial poem to trace the author's ideological position. The findings indicate that the text reflects the inclusive and cosmopolitan character of Zabid society, marked by dynamic Sufi traditions and complex inter-school relations. Consequently, this study offers a more balanced understanding of Maulid al-Dība'i as a product of Islamic culture shaped by historical and spiritual struggles.